Implementasi Program Kuliah Kerja Nyata: Pembuatan dan Pengelolaan Bank Sampah Edukatif di Desa Polewali Marajae, Kecamatan Batulicin - Ridwan, Muhammad; Harnaini, Herli; Helpiana, Eka; Pratiwi, Lestari Ayu; Kamalia, Kamalia; Mardianawati, Siti; Mirnawati, Mirnawati; Handayani, Pitri; Cahya, Wulan; Hamimah, Siti (Universitas Negeri Gorontalo, 2025)
KKN (Kuliah Kerja Nyata) is a community service activity carried out by university students as part of the implementation of the Tri Dharma of Higher Education. This activity aims to raise public awareness regarding proper waste management through the creation and management of an educational waste bank in Polewali Marajae Village, Batulicin District. The program focused on household waste management through several steps: the establishment of a waste bank, the creation of banners differentiating organic and inorganic waste, and the distribution of waste bins and educational banners at several strategic points such as the village office yard, volleyball court, and Polewali Marajae Elementary School. The method used was a participatory approach, involving the community in every stage of implementation. The results of the activity showed an increase in public awareness regarding waste separation and the production of quality compost from organic waste. This activity demonstrates that an educational waste bank can be an effective means of cultivating environmentally friendly behavior in rural communities.